2020
DOI: 10.1097/psy.0000000000000890
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder and Persistent Somatic Symptoms During the COVID-19 Pandemic: The Role of Sense of Threat

Abstract: Objective: Persistent somatic symptoms, such as pain and fatigue, have been referred to as somatization. Somatization is commonly associated with histories of trauma and posttraumatic stress disorder (PTSD). Although previous research has demonstrated that PTSD can predict somatic problems, there has been no examination of this at the level of PTSD symptom clusters and multidimensional assessment of somatic symptoms. We examined the association between the three International Classification of Disease (11th Ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…[56,57] Various studies also highlight that stressrelated symptoms that may be included in the diagnostic criteria for PTSD are strongly related to somatic symptoms in the COVID-19 era. [58][59][60] On the other hand, the second most significant predictor in the model of this study was found to be the level of PR, which worked as a protective factor for psychosomatic health. In Greece, little evidence supported the link between psychosomatic health and resilience before the COVID-19 outbreak.…”
Section: Comparing the Findings With Previous Studiesmentioning
confidence: 55%
“…[56,57] Various studies also highlight that stressrelated symptoms that may be included in the diagnostic criteria for PTSD are strongly related to somatic symptoms in the COVID-19 era. [58][59][60] On the other hand, the second most significant predictor in the model of this study was found to be the level of PR, which worked as a protective factor for psychosomatic health. In Greece, little evidence supported the link between psychosomatic health and resilience before the COVID-19 outbreak.…”
Section: Comparing the Findings With Previous Studiesmentioning
confidence: 55%
“…Notably, participants' ratings of distress about COVID-19 symptoms and illness in themselves and friends and family were associated with increased symptoms of somatization. Consistent with Motivated Cue-Integration theory (Shalev, 2021) in the context of COVID-19, a lack of certainty about the facts of the disease in the spring of 2020, especially concerning its effects on pregnancy, known variability in symptom presentation, and a heightened sense of threat (Jowett et al, 2021) may have contributed to hypervigilant monitoring of physical symptoms.…”
Section: Discussionmentioning
confidence: 88%
“…Fewer studies have examined maternal somatization in relation to offspring functioning. Nevertheless, given the increase in somatization documented during the pandemic (Jowett et al, 2021;Ran et al, 2020), we hypothesized that maternal somatization would affect infant temperament. Although we did not collect biological specimens in our study to elucidate mechanisms that might underlie the relations between maternal mental health and infant temperament, prior research testing the Developmental Origins of Health and Disease hypothesis (Gluckman et al, 2007) implicates epigenetic, neuroendocrine, and/or inflammatory pathways in this association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The suggested higher relative importance of psychosocial drivers in the PCS phase may inform more holistic assessment and treatment strategies, including psychological and psychosocial supports. Additionally, the frequent presence of psychological distress may be linked to several reported symptoms, with a range of psychological disorders often associated with hair loss (61), sleep disorders (62), gastrointestinal issues (63), pain (64), and cardiovascular symptoms (64).…”
Section: Meaning Of the Studymentioning
confidence: 99%